2022
DOI: 10.1001/jamanetworkopen.2022.30439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dimethyl Fumarate vs Interferon β-1a in Patients With Pediatric-Onset Multiple Sclerosis

Abstract: ImportanceWith few approved multiple sclerosis therapies in the pediatric population, there is a need for further approved treatment options. Limited data exist for dimethyl fumarate (DMF) treatment in pediatric-onset multiple sclerosis (POMS).ObjectiveTo compare the efficacy, safety, and tolerability of DMF vs intramuscular interferon β-1a (IFNβ-1a) in POMS.Design, Setting, and ParticipantsThe CONNECT study was an active-controlled, open-label, rater-blinded 96-week randomized clinical trial in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The pediatric labeling of fingolimod makes it the first and only currently US Food and Drug Administration–approved DMT for children. Of note, results from the CONNECT trial were published in 2022, which found dimethyl fumarate to be superior to interferon β in children with MS based on similar end points . How these new findings will affect future trends in DMT use in children remains to be seen.…”
Section: Discussionsupporting
confidence: 74%
“…The pediatric labeling of fingolimod makes it the first and only currently US Food and Drug Administration–approved DMT for children. Of note, results from the CONNECT trial were published in 2022, which found dimethyl fumarate to be superior to interferon β in children with MS based on similar end points . How these new findings will affect future trends in DMT use in children remains to be seen.…”
Section: Discussionsupporting
confidence: 74%
“…39 Herein, DMF was classified among MET based on the most conservative assumption because no robust RCT has yet shown that DMF is more effective than platform therapies or teriflunomide, neither in adults nor children. 4,40,41 Limiting long-term disability is critical, but no differences were found between strategies, possibly due to missing baseline EDSS scores and a relatively short follow-up duration, as in other studies. 10 Yet, we cannot rule out that patients initially treated with MET who escalated to HET were ultimately sufficiently protected against EDSS progression at 5 years.…”
Section: Discussionmentioning
confidence: 96%
“…1,2 Teriflunomide and DMF were recently approved by the US Food and Drug Administration and European Medicine Agency following the phase 3 Efficacy, Safety, and Pharmacokinetics of Teriflunomide in Pediatric Patients With Relapsing Forms of Multiple Sclerosis (TERIKIDS) and Phase 3 Efficacy and Safety Study of BG00012 in Pediatric Subjects With Relapsing-Remitting Multiple Sclerosis (CONNECT) RCTs. [3][4][5] These successes paved the way for other ongoing RCTs with highly potent drugs like ocrelizumab, ofatumumab, and siponimod. 6,7 In the last decade, the availability of highly potent drugs led to a decrease in long-term disability accrual.…”
mentioning
confidence: 99%
“…In addition, the results suggested that delaying DMT at an early stage of MS could lead to a decrease in the cumulative efficacy of DMT treatment when patients are older [31]. In pediatric patients with MS aged 10-17 years, DMF has been shown to be more effective than IFNb-1a in that more patients were free of new or newly enlarging T2 lesions following 96 weeks of treatment with DMF compared with IFNb-1a (16% vs. 5%, respectively) [32]. These studies provide further evidence of the beneficial effects of early and consistent treatment with DMF.…”
Section: Discussionmentioning
confidence: 96%